2015
DOI: 10.1371/journal.pone.0137247
|View full text |Cite
|
Sign up to set email alerts
|

Balanced Hydroxyethylstarch (HES 130/0.4) Impairs Kidney Function In-Vivo without Inflammation

Abstract: Volume therapy is a standard procedure in daily perioperative care, and there is an ongoing discussion about the benefits of colloid resuscitation with hydroxyethylstarch (HES). In sepsis HES should be avoided due to a higher risk for acute kidney injury (AKI). Results of the usage of HES in patients without sepsis are controversial. Therefore we conducted an animal study to evaluate the impact of 6% HES 130/0.4 on kidney integrity with sepsis or under healthy conditions Sepsis was induced by standardized Colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…The lower molecular weight, lower substitution grade, and high C2:C6 substitution ratio theoretically should decrease adverse effects on coagulation and renal damage. Although reports in human medicine are inconsistent in terms of HES type, and additional factors such as the presence of sepsis affect pathophysiological changes, present veterinary studies may suggest that HES‐130/0.4 is less likely than pentastarch to induce AKI or increase AKI grade in dogs if used at moderate dosages.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The lower molecular weight, lower substitution grade, and high C2:C6 substitution ratio theoretically should decrease adverse effects on coagulation and renal damage. Although reports in human medicine are inconsistent in terms of HES type, and additional factors such as the presence of sepsis affect pathophysiological changes, present veterinary studies may suggest that HES‐130/0.4 is less likely than pentastarch to induce AKI or increase AKI grade in dogs if used at moderate dosages.…”
Section: Discussionmentioning
confidence: 81%
“…Whereas histopathological changes are seen within 24 hours after exposure, increases in serum creatinine concentrations may lag behind the development of AKI . In another study, serum creatinine concentration peaked at day 3, yet another study showed an increase in serum creatinine concentration within 24 hours of HES application to septic rats .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the difference between septicemic patients and other populations, the renal impairment seems to occur independent of inflammation even though changes are pronounced with concurrent sepsis in a rat model of septic AKI. 24 Renal injury induced by HES treatment therefore might be more severe and clinically important in septic patients, requiring further studies in both septicemic dogs and cats.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, increases in serum creatinine concentrations are expected within 2-4 days after renal injury and renal injury by HES has been identified histologically after 24 hours of HES administration. 10,[23][24][25] We therefore defined short-term evaluation as changes between baseline and 2-10 days and long-term evaluation as changes between baseline and 11-90 days. The low number of animals available for long-term analysis and median days of last creatinine determination being <20 days limits our findings regarding long-term evaluation and linear regression analysis investigating potential risk factors for a long-term effect of HES therefore was not performed.…”
Section: Discussionmentioning
confidence: 99%
“…Information about the HES mediated physiological and cellular mechanisms that are responsible for the adverse effects of HES in specific organs is very scarce and has mainly been described in the heart [ 5 ] and kidney [ 6 ]. Unexpectedly, animal studies even showed positive effects of HES on inflammatory processes during sepsis [ 7 – 10 ] and concerning the negative effects of HES solutions on vascular permeability in the heart, some studies suggested that addition of Alb to HES containing solutions might be beneficial and could have the potential to reduce the adverse effects of HES [ 5 , 11 ].…”
Section: Introductionmentioning
confidence: 99%